Síntese de nanopartículas de ZrO2/SO42- e ZrO2/Fe3+ por método solvotérmico e aplicação na catálise de reações de esterificação - Pegoraro, Guilherme Manassés (2024)
With the advent of nanotechnology and the production of nanostructured materials, research in recent decades has identified that it is often possible to improve the physical-chemical properties of materials by changing their scale. Zirconium oxide (ZrO2), studied in this work, presents catalytic properties for some chemical reactions. When producing nanoparticles of this material, the specific surface area is increased, where catalysis occurs. Among the catalyzed reactions, esterification stands out, which is relevant to produce biodiesel as a renewable alternative to fossil fuels. Pure, sulfated or iron(III) doped zirconium oxide were synthesized by the solvothermal route with and without microwave incidence. Both synthesis routes allowed obtaining powders with similar yields, and sulfate functionalization was confirmed by Fourier transform infrared spectroscopy (FTIR). This technique also provided evidence that the washing steps were not able to eliminate all the organic residue adsorbed on ZrO2. Scanning electron microscopy (SEM) and dynamic light scattering (DLS) results indicated that the material was highly agglomerated, but that there were particles smaller than a few micrometers. After analysis by energy dispersive X-ray spectroscopy (EDS), there was a strong indication of the formation of the desired material, as well as the presence of iron(III) as a dopant and the presence of carbon and chlorine in the material, coming from the synthesis route. X-ray diffractometry (XRD) showed that the samples synthesized on the heating plate crystallized in the tetragonal structure with an average crystallite size varying between 2 and 7 nm, while with microwave incidence there was an amorphous structure. The ideal calcination parameters were determined with the XRD technique, noting that calcination for 30 minutes at 500 ºC was enough for crystallization in the tetragonal phase, doubling the crystallite size of some samples, varying between 7 and 16 nm, in addition to eliminating the adsorbed residues. The nanoparticles were applied in the catalysis of the esterification between oleic acid and methanol or ethanol at 60 ºC. The conversion rates were determined through the elaboration of calibration curves and the deconvolution of carbonyl peaks in the infrared spectra of the reaction products. Catalytic activity was noted for practically all pure, functionalized and doped samples, with iron(III) doped samples having the best performance, such as ZrO2/Fe3+ sample produced with the heating plate, with 86.3% conversion.